Microbial biotransformation – an important tool for the study of drug metabolism. (3rd August 2019) - Salter, Rhys; Beshore, Douglas C.; Colletti, Steven L.; Evans, Liam; Gong, Yong; Helmy, Roy; Liu, Yong; Maciolek, Cheri M.; Martin, Gary; Pajkovic, Natasa; Phipps, Richard; Small, James; et al.
Abstract: Metabolite identification is an integral part of both preclinical and clinical drug discovery and development. Synthesis of drug metabolites is often required to support definitive identification, preclinical safety studies and clinical trials. Here we describe the use of microbial biotransformation as a tool to produce drug metabolites, complementing traditional chemical synthesis and other biosynthetic methods such as hepatocytes, liver microsomes and recombinant human drug metabolizing enzymes. A workflow is discussed whereby microbial strains are initially screened for their ability to form the putative metabolites of interest, followed by a scale-up to afford quantities sufficient to perform definitive identification and further studies. Examples of the microbial synthesis of several difficult-to-synthesize hydroxylated metabolites and three difficult-to-synthesize glucuronidated metabolites are described, and the use of microbial biotransformation in drug discovery and development is discussed.